Teaching practice and digital technologies - Gonçalves, Adriana De Marchi (2021)
The purpose of this article was to identify how vocational education teachers see the use of digital technology in their teaching practice. The adopted methodology included qualitative research based on bibliographic sources that contributed to the reflection on digital technologies in education. The evolution of teaching practice tends to be continuous and appropriate to the daily context in the classroom, and includes the use of digital information and communication technologies (TDIC, Brazilian acronym) for the construction of student knowledge, making learning effective. In this sense, it is concluded that the teacher becomes a mediator of learning, and that the continuing education of teachers is fundamental for teaching practice. Keywords: Professional Education. Teaching Practice. Digital Technology. Teacher Training.